Identifying, Analyzing, and Communicating Rural: A Quantitative Perspective - Natalie A. Koziol; Ann M. Athur; Leslie R. Hawley; James A. Bovaird; Kirstie L. Bash; Carina McCormick; Greg W. Welch (Journal of Research in Rural Education, 2015)
Defining rural is a critical task for rural education researchers, as it has implications for all phases of a study. However, it is also a diffi cult task due to the many ways in which rural can be theoretically, conceptually, and empirically operationalized. This article provides researchers with specifi c guidance on important theoretical and operational considerations relevant to conducting quantitative rural education research: identifying a rural defi nition, selecting appropriate analytic methods, and thoroughly communicating rural details to situate the fi ndings within the broader rural literature base. In addition, this article uses the Early Childhood Longitudinal Study, Kindergarten Class of 1998-99 (ECLS-K) and three rural defi nitions to illustrate how parameter estimates and substantive interpretations are impacted by the statistical model, rural defi nition, and exclusion/inclusion of covariates. We believe that informed consideration and implementation of the article's guidelines will enhance and clarify the quantitative literature on rural education.